Transfer of the monospecific genus Nienburgella (Delesseriaceae, Rhodophyta) to Phycodrys, based on morphological and molecular evidence - Kang, Jeong Chan; Lee, Hyung Woo; Kim, Myung Sook (Phytotaxa, 2021)
The genus Phycodrys is characterized by having a Phycodrys-type apical organization, a well-developed central midrib with paired lateral veins, monostromatic areas between the veins, four-celled carpogonial branches with two groups of sterile cells, and a cystocarp with a large fusion cell and short-catenated carposporangia. In contrast, the monospecific genus Nienburgella has a faint midrib, a mostly polystromatic blade without lateral veins, bilaterally isometric second-order cell row length, and Phycodrys-like apical growth and cystocarp. Nothing is known about Nienburgella’s procarp. We collected several specimens of Nienburgella angusta from the East Sea of South Korea and noticed that they resemble Phycodrys radicosa. We compared these two species using morphological and molecular phylogenetic analyses. Our results revealed that both species are closely related to one another than to other taxa in the tribe Phycodryeae, and that Nienburgella angusta procarp developmental pattern is the same as the one observed in Phycodrys rubens, the generitype species of Phycodrys. Thallus structure (mono- or polystromatic) was species-delimiting but not genus-delimiting. Bilateral second-order cell row isometry occurs in other Phycodrys species, including the type species. Therefore, we propose transferring the species Nienburgella angusta as well as the monospecific genus Nienburgella to Phycodrys.